PENGARUH GANGGUAN BAHASA TERHADAP KEMAMPUAN BICARA PADA ANAK GAGAP USIA 7-10 TAHUN - Lutvi Qolbiyatu Zuhro NH; Miftahul Hasan; Vella Julia; Fisnia Pratami (CV. Denasya Smart Publisher, 2024)
The study analyzes developmental stuttering in children aged 7-10 years in elementary school. It uses a descriptive qualitative method through observation, audio recordings, and interviews. The findings show that stuttering is caused by anxiety, fear, and low self-confidence, especially in stressful situations. Support from family, teachers, a positive environment, and relaxed speaking practice effectively improve speech fluency. If stuttering persists, consulting a speech therapist or psycologist is highly recommended.